Hepatitis B Virus Precore Protein p22 Inhibits Alpha Interferon Signaling by Blocking STAT Nuclear Translocation - Mitra, Bidisha; Wang, Jinyu; Kim, Elena S.; Mao, Richeng; Dong, Minhui; Liu, Yuanjie; Zhang, Jiming; Guo, Haitao (Journal of virology, 2019)
Chronic hepatitis B virus (HBV) infection continues to be a major global health concern, and patients who fail to mount an efficient immune response to clear the virus will develop a life-long chronic infection that can progress to chronic active hepatitis, cirrhosis, and primary hepatocellular carcinoma. There is no definite cure for chronic hepatitis B, and alpha interferon (IFN-α) is the only available immunomodulatory drug, to which only a minority of chronic patients are responsive, with hepatitis B e antigen (HBeAg)-negative patients responding better than HBeAg-positive patients. We herein report that the intracellular HBeAg, also known as precore or p22, inhibits the antiviral signaling of IFN-α, which sheds light on the enigmatic function of precore protein in shaping HBV chronicity and provides a perspective toward areas that need to be further studied to make the current therapy better until a cure is achieved. Antagonism of host immune defenses against hepatitis B virus (HBV) infection by the viral proteins is speculated to cause HBV persistence and the development of chronic hepatitis. The circulating hepatitis B e antigen (HBeAg, p17) is known to manipulate host immune responses to assist in the establishment of persistent viral infection, and HBeAg-positive (HBeAg + ) patients respond less effectively to IFN-α therapy than do HBeAg-negative (HBeAg − ) patients in clinical practice. However, the function(s) of the intracellular form of HBeAg, previously reported as the precore protein intermediate (p22) without the N-terminal signal peptide, remains elusive. Here, we report that the cytosolic p22 protein, but not the secreted HBeAg, significantly reduces interferon-stimulated response element (ISRE) activity and the expression of interferon-stimulated genes (ISGs) upon alpha interferon (IFN-α) stimulation in cell cultures. In line with this, HBeAg + patients exhibit weaker induction of ISGs in their livers than do HBeAg − patients upon IFN-α therapy. Mechanistically, while p22 does not alter the total STAT1 or pSTAT1 levels in cells treated with IFN-α, it blocks the nuclear translocation of pSTAT1 by interacting with the nuclear transport factor karyopherin α1 through its C-terminal arginine-rich domain. In summary, our study suggests that HBV precore protein, specifically the p22 form, impedes JAK-STAT signaling to help the virus evade the host innate immune response and, thus, causes resistance to IFN therapy. IMPORTANCE Chronic hepatitis B virus (HBV) infection continues to be a major global health concern, and patients who fail to mount an efficient immune response to clear the virus will develop a life-long chronic infection that can progress to chronic active hepatitis, cirrhosis, and primary hepatocellular carcinoma. There is no definite cure for chronic hepatitis B, and alpha interferon (IFN-α) is the only available immunomodulatory drug, to which only a minority of chronic patients are responsive, with hepatitis B e antigen (HBeAg)-negative patients responding better than HBeAg-positive patients. We herein report that the intracellular HBeAg, also known as precore or p22, inhibits the antiviral signaling of IFN-α, which sheds light on the enigmatic function of precore protein in shaping HBV chronicity and provides a perspective toward areas that need to be further studied to make the current therapy better until a cure is achieved.